Repeated photodynamic therapy mediates the abscopal effect through multiple innate and adaptive immune responses with and without immune checkpoint therapy. (January 2023) - Lou, Jenny; Aragaki, Masato; Bernards, Nicholas; Chee, Tess; Gregor, Alexander; Hiraishi, Yoshihisa; Ishiwata, Tsukasa; Leung, Chelsea; Ding, Lili; Kitazawa, Shinsuke; Koga, Takamasa; Sata, Yuki; et al.
Abstract: In combination with immune checkpoint inhibitors, photodynamic therapy can induce robust immune responses capable of preventing local tumor recurrence and delaying the growth of distant, untreated disease (ie. the abscopal effect). Previously, we found that repeated photodynamic therapy (R-PDT) using porphyrin lipoprotein (PLP) as a photosensitizer, without the addition of an immune checkpoint inhibitor, can induce the abscopal effect. To understand why PLP mediated R-PDT alone can induce the abscopal effect, and how the addition of an immune checkpoint inhibitor can further strengthen the abscopal effect, we investigated the broader immune mechanisms facilitated by R-PDT and combination R-PDT + anti-PD-1 monoclonal antibody (αPD-1) in a highly aggressive, subcutaneous AE17-OVA mesothelioma dual tumor-bearing C57BL/6 mice. We found a 46.64-fold and 61.33-fold increase in interleukin-6 (IL-6) after R-PDT and combination R-PDT + αPD-1 relative to PBS respectively, suggesting broad innate immune activation. There was a greater propensity for antigen presentation in the spleen and distal, non-irradiated tumor draining lymph nodes, as dendritic cells and macrophages had increased expression of MHC class II, CD80, and CD86, after R-PDT and combination R-PDT + αPD-1. Concurrently, there was a shift in the proportions of CD4+ T cell subsets in the spleen, and an increase in the frequency of CD8+ T cells in the distal, non-irradiated tumor draining lymph nodes. While R-PDT had an acceptable safety profile, combination R-PDT + αPD-1 induced 1.26-fold higher serum potassium and 1.33-fold phosphorus, suggestive of mild laboratory tumor lysis syndrome. Histology revealed an absence of gross inflammation in critical organs after R-PDT and combination R-PDT + αPD-1 relative to PBS-treated mice. Taken together, our findings shed light on how the abscopal effect can be induced by PDT and strengthened by combination R-PDT + αPD-1, and suggests minimal toxicities after R-PDT.